Design, Synthesis and Structure-Activity Relationship Studies of 6-Phenyl-4,5-dihydro-3(2H)-pyridazinone Derivatives as Cardiotonic Agents - Wang, Teng; Dong, Ying; Wang, Li-Chen; Xiang, Bing-Ren; Chen, Zhen; Qu, Ling-Bo (Arzneimittelforschung, 2008)
Based on our previous study, a variety of 12 novel 6-phenyl-4,5-dihydro-3(2H)-pyridazinone derivatives were synthesized. The structures attributed to the compounds were elucidated using IR, 1H-NMR and mass spectra. The cardiotonic activities of these compounds were assessed by Straub’s perfusion method and a clear cardiotonic effect was shown for compounds 1c (2,3-dichloro-N-(4-(4-methyl-6-oxo-l,4,5,6-tetrahydro-pyridazin-3-yl)phenyl) benzamide), 1d (4-amino-3-methyl-N-(4-(4-methyl-6-oxo-1,4,5,6-tetrahydropyridazin-3-yl) phenyl)benzamide), 2a (3-methyl-4-nitro-N-(4-(6-oxo-l,4,5,6-tetrahydro-pyridazin-3-yl)phenyl)benzamide) and 2d (4-amino-3-methyl-N-(4-(6-oxo-1,4,5,6-tetrahydropyridazin-3-yl)phenyl) benzamide) when compared to another 3 (2H)-pyridazinone derivative, levosim-endan (CAS 141505-33-1). The structure activity relationships of the compounds were studied using the rough sets theory.
Keywords: Cardiotonic agents; CAS 141505-33-1; Levosimendan; 3(2H)-Pyridazinones, cardiotonic activity, structure-activity relationship, synthesis